MODAL SOSIAL DALAM PENGEMBANGAN WISATA ALAM BUKIT CONDONG DI KELURAHAN SELENSEN KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - Muardi Khotib; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Social Capital in the Development of Bukit Condong Nature Tourism at Selensen Village, Kemuning District, Indragiri Hilir Regency. The purpose of this study was to determine how social capital and the conditions that support and inhibit the development of natural tourism in Bukit Condong at Selensen Village, Kemuning District, Indragiri Hilir Regency. The theory used in this research is the social capital theory put forward by Coleman which consists of trust, network, and norms. This type of research uses descriptive qualitative research methods. The subjects of this study amounted to 5 people consisting of the community, including youth who participated in the development effort of the Bukit Lean natural tourism. data sources used are primary data sources and secondary data. Data collected by data collection techniques in the form of observation, interviews and documentation. Data analysis used in this study was data reduction, data presentation and conclusion drawing. The results of this study are social capital which is very important in a development, or networks, beliefs, and norms that play an important role in the development of the Bukit Condong Nature Tourism at Selensen Village, Kemuning District, Indragiri Hilir Regency. Network is a link that connects individuals with other individuals or between groups with other groups which has a positive impact as in establishing cooperation in the development of this natural tourism. Trust is the basis for the relationship between actors in activities. Social norms such as methods, habits, behavior and customs are the social rules of life. Keywords: Social Capital, Natural Tourism Development